How management innovations are successfully implemented? An organizational routines' perspective. Issue 4 (3rd July 2017) - Lin, Haifen; Chen, Mengya; Su, Jingqin
Abstract : Purpose: The purpose of this paper is to address how management innovations are implemented deeply at the most micro level of organizations, namely, organizational routines, or to investigate the process through which organizational routines evolve in implementing management innovations, with existing routines overturned and new routines created and solidified. Design/methodology/approach: This paper adopts an interpretive and exploratory case study on the case of Day-Definite (DD) innovation which has successfully brought Arima World Group Company Limited (HOAU) into a new value-added arena, in terms of timing, security and high service quality. Considering that DD innovation reflects a systematic innovation of the whole organization, this paper focuses on it to explore the complex implementation mechanism of management innovation. Multiple approaches were utilized during data collection to meet criteria for trustworthiness, including semi-structured interviews, archival data and observation; and the data analysis went through a five-step process. Findings: The results confirm management innovation as a complex project concerning organizational routines which represent a central and fundamental element of organizations. Also, it finds that organizational routines evolve in innovation implementation through a three-phase process consisting of the existing-routine-domination phase, the new-routine-creation phase and -solidification phases, each exhibiting different innovation activities and characteristics of participants' cognition and behaviors; recreation of new routines is the key for routine evolution, thus for success of management innovations. Research limitations/implications: This research is constrained by several limitations. The set-up framework of organizational routine evolution in innovation implementation needs a further confirmation in more organizations; other elements, such as cognition of managers, resource orchestration, environmental elements or organizational culture, should be considered for the success of innovation implementation; and more attention should be paid to the potential power asymmetries among participants and its potential influence on forming shared schemata and subsequent new routines, besides interactions and role taking. Originality/value: The findings offer some valuable insights for further research on management innovation and organizational routines and hold important implications for management practices. This research extends research on management innovation and the Kurt Lewin Change Theory and Change Model to explore innovation implementation at a most micro level; furthers research on organizational routines, especially routine dynamic theory, by holding the two-component view and exploring the process through which organizational routines evolve; and contributes to research on the relationship between organizational routines and innovations by taking an organizational routines' perspective. It reminds managers of the depth and complication of innovation implementation.